1976
DOI: 10.1104/pp.58.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ethylene Production by Cobaltous Ion

Abstract: The effect of Co2+ on ethylene production by mung bean (Phaseolus aureus Roxb.) and by apple tissues was studied. Co2+, depending on concentrations applied, effectively inhibited ethylene production by both tissues. It also strongly inhibited the ethylene production induced by IAA, kinetin, IAA plus kinetin, Ca2+, kinetin plus Ca22, or Cu2+ treatments in mung bean hypocotyl segments. While Co2+ greatly inhibited ethylene production, it had little effect on the respiration of apple tissue, indicating that Co2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
3

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(76 citation statements)
references
References 30 publications
3
70
0
3
Order By: Relevance
“…In accordance with these results, it has been shown that ethylene production from excised root tips doubled after 15 min of aluminium treatment [43]. It is well known that cobalt inhibits ethylene production in root tissues, both during non stressful or stressful conditions [44]. The present study demonstrated that cobalt effectively alleviated both ACC-and Cd-induced root growth inhibition and root swelling, further suggesting a crucial role of enhanced ethylene synthesis in the response of roots to Cd.…”
Section: A B Csupporting
confidence: 78%
“…In accordance with these results, it has been shown that ethylene production from excised root tips doubled after 15 min of aluminium treatment [43]. It is well known that cobalt inhibits ethylene production in root tissues, both during non stressful or stressful conditions [44]. The present study demonstrated that cobalt effectively alleviated both ACC-and Cd-induced root growth inhibition and root swelling, further suggesting a crucial role of enhanced ethylene synthesis in the response of roots to Cd.…”
Section: A B Csupporting
confidence: 78%
“…AgNO 3 has been reported to inhibit ethylene action (Beyer, 1976), and cobalt ions are known to inhibit ethylene production (Lau and Yang, 1976). It was found that addition of AgNO 3 to the culture media greatly improves regeneration of many dicot and monocot cultures as in case of Coffea sp., and Vanilla planifolia ) and even somatic embryogenesis in Coffea species ).…”
Section: Discussionmentioning
confidence: 90%
“…Silver (silver nitrate as ethylene action inhibitor) and cobalt ions (cobalt chloride is an ethylene biosynthesis inhibitor), are also known to be involved in flower induction and other phenotypic responses (Bais et al 2000;Obul Reddy et al 2001). Cobalt chloride effectively inhibits ethylene production and substantially increases shoot regeneration by blocking the conversion of ACC to ethylene (Lau and Yang, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…and Kozlowski, 1982), water stress (Morgan . 1990) and heavy metals (Lau and Yang, 1976 ;Tingey, 1980). But there is little data about ethylene release from intact plants under stress.…”
Section: Effects Of Ethylene On Morphology and Growth Of Plantsmentioning
confidence: 99%